Interactive Webgis for Mapping and Monitoring Urban Drainage Systems - Muhamad Adam; Somantri Somantri; Imam Sanjaya (Komunitas Dosen Indonesia, 2025)
The development of infrastructure and changes in land use in urban areas increase surface runoff that cannot be properly managed, posing a flood risk if the drainage channel capacity is inadequate. To address the lack of an integrated information system for drainage monitoring, this study developed a WebGIS system based on Laravel, QGIS, and LeafletJS using the Rapid Application Development (RAD) approach. The system is designed to support the Department of Public Works and Spatial Planning (DPUTR) of Sukabumi City in monitoring and mapping the distribution and condition of drainage channels interactively and in real-time. The WebGIS integrates spatial data (Linestring geometry) and non-spatial data (condition attributes, length, and road location), and provides features such as search, condition filters, and elevation contour layers. System testing was conducted using the Black-box method and Lighthouse tools to assess functionality and performance. The results showed scores of 91 for accessibility, 79 for performance (mobile), 72 for best practices, and 92 for SEO, indicating a user-friendly interface that complies with web development standards. The system is considered effective in improving drainage infrastructure management, supporting spatial-based decision-making, and enhancing public information transparency. Therefore, this system serves as a replicable WebGIS model for other cities facing similar drainage management challenges.